EFEK MODERASI KONDISI LINGKUNGAN SEKOLAH PADA PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR - Ririn Nurhayati; Neti Budiwati; Kinanti Geminastiti Hilmiatussadiah (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
This research is motivated by the large number of students who obtain learning outcomes under the KKM and low national examination results. This study aims to determine the general picture and determine the effects of moderation in the school environment on the influence of student learning discipline on student learning outcomes. The method used is an explanatory survey by giving questionnaires to students. The population in this study were 1,622 students with Non Probability Sampling techniques using a sample of 732 students. The data analysis technique used is Multiple Regression Analysis (ARM). The results showed that: (1) Student learning discipline had a positive effect on student learning outcomes, (2) The condition of the school environment moderated the effect of student learning discipline on student learning outcomes.